Effect Fluctuations in MFO and HSD Fuel Prices Against Current Indonesian Sea Freight Passengers and Cargo (April 2023 – April 2024) - Ramadhani, Nafalla Puteri; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This research aiming For analyze impact fluctuation price material burn to the volume of goods transported through transport sea , with approach descriptive quantitative . Data obtained from report operational company shipping and publication price material burn in period five years time last . Introduction explain importance efficiency cost operational in increase Power competition transport sea . Methodology study covers secondary data collection and analysis regression For measure connection between price material fuel and volume of goods transported . Research results show that increase price material burn , like High-Speed Diesel (HSD) and Marine Fuel Oil (MFO), contribute significant to improvement cost operational , which has an impact on reducing the volume of transportation goods . On the other hand , the decline price material burn influential positive to increase in transport volume sea . Discussion underline factor external , such as price world oil and policy domestic , which also influence stability operational voyage . The conclusion suggests importance implementation policy adaptive and management operational based on efficiency For guard stability sector transportation sea in face dynamics price global energy . This research give contribution to planning strategic in the sector maritime , especially in mitigation risk consequence fluctuation price material burn.